'More Human than Human': Colonial Logics and the Modern Subject in Science Fiction Films. (October 2022) - Martins Simoneti, Caio A.
Science fiction has often been associated with colonial imaginaries, given its engagement with themes such as invasions and encounters with other civilisations. This article addresses these relations by focusing on the invasion plot subgenre and the nexus between the modern subject and colonial frameworks. It argues that conceptions of subjectivity are a site of symbolic struggle, acting not only as the bases of the reproduction of colonial logics in these narratives, but also as a locus for their disruption. It first analyses Independence Day and War of the Worlds, highlighting how categories such as disembodiment, anthropocentrism and linear progress are crucial in reproducing the modern subject and colonial hierarchies in invasion stories. It then explores Arrival and Annihilation to argue that invasion plots can also present alternative forms of encounter as they disrupt modern subjectivity and colonial frameworks by contesting ideas of disembodiment, identity, progress and the human/nonhuman divide.